Chemotherapy reinforces anti-tumor immune response and enhances clinical efficacy of immune checkpoint inhibitors - Zhang, Lin; Zhou, Chao; Zhang, Songou; Chen, Xiaozhen; Liu, Jian; Xu, Fangming; Liang, Wenqing (Frontiers in Oncology, 2022)
New evidence suggests that the clinical success of chemotherapy is not merely due to tumor cell toxicity but also arises from the restoration of immunosurveillance, which has been immensely neglected in previous preclinical and clinical researches. There is an urgent need for novel insights into molecular mechanisms and regimens that uplift the efficacy of immunotherapy since only a minority of cancer patients are responsive to immune checkpoint inhibitors (ICIs). Recent findings on combination therapy of chemotherapy and ICIs have shown promising results. This strategy increases tumor recognition and elimination by the host immune system while reducing immunosuppression by the tumor microenvironment. Currently, several preclinical studies are investigating molecular mechanisms that give rise to the immunomodulation by chemotherapeutic agents and exploit them in combination therapy with ICIs in order to achieve a synergistic clinical activity. In this review, we summarize studies that exhibit the capacity of conventional chemotherapeutics to elicit anti-tumor immune responses, thereby facilitating anti-tumor activities of the ICIs. In conclusion, combining chemotherapeutics with ICIs appears to be a promising approach for improving cancer treatment outcomes.